Inductively Coupled Telemetry in Spinal Fusion Application Using Capacitive Strain Sensors - Lin, Ji-Tzuoh; Jackson, Douglas; Aebersold, Julia; Walsh, Kevin; Naber, John; Hnat, William (IntechOpen, 2011)
None